PENGEMBANGAN KOMPETENSI KEWIRAUSAHAAN MASYARAKAT PESISIR MELALUI INOVASI PRODUK KERIPIK RUMPUT LAUT DI KOTA TARAKAN - AB, Nizhamuddin; Suryana, Nia Kurniasih; Sudarto, Sudarto; Juliana, Ahmad; Syahran, Syahran; Cahyaningrum, Widyastuti; Giggs, Naybila (Universitas Padjadjaran, 2026)
Coastal communities in Tarakan City have considerable potential to develop seaweed as a local economic commodity. However, its utilization remains largely dominated by raw material sales, resulting in limited added economic value for local business actors. This community service program aimed to strengthen the entrepreneurial competence of coastal communities through seaweed-cracker product innovation based on training, business mentoring, appropriate technology diffusion, and digital marketing. The program was implemented with the Usaha Wanita Pantai Amal partner group using a participatory approach, including needs identification, production process observation, focus group discussions, practical training, mentoring, and monitoring and evaluation. The intervention involved the use of stainless steel gas ovens and oil spinners, improvements in production hygiene, simple financial record-keeping, packaging innovation, branding, and digital marketing. The final evaluation showed that production capacity increased by 30%, production efficiency rose by 35%, digital marketing utilization increased from 10% to 40%, and 75% of partner members began applying simple financial record-keeping. In addition, the partners' level of empowerment in the production and management-marketing aspects increased from a score of 1 to a score of 3 based on observation and mentoring evaluations. The novelty of this program lies in the development of a coastal community-based seaweed innovation model that integrates appropriate technology, entrepreneurial competence strengthening, and collective business institutional readiness through the initiation of a Joint Business Group. These findings indicate that product innovation based on local potential can strengthen the competitiveness of coastal MSMEs and provide a foundation for replicating similar empowerment programs in other coastal communities. Masyarakat pesisir Kota Tarakan memiliki potensi rumput laut sebagai komoditas ekonomi lokal, namun pemanfaatannya masih didominasi penjualan bahan mentah sehingga nilai tambah ekonomi yang diperoleh pelaku usaha masih terbatas. Program pengabdian ini bertujuan memperkuat kompetensi kewirausahaan masyarakat pesisir melalui inovasi produk keripik rumput laut berbasis pelatihan, pendampingan usaha, difusi teknologi tepat guna, dan pemasaran digital. Kegiatan dilaksanakan bersama mitra Usaha Wanita Pantai Amal dengan pendekatan partisipatif melalui identifikasi kebutuhan, observasi proses produksi, diskusi kelompok terfokus, pelatihan praktik, pendampingan, serta monitoring dan evaluasi. Intervensi program mencakup penggunaan oven gas stainless dan mesin spinner, penguatan higienitas produksi, pencatatan keuangan sederhana, inovasi kemasan, branding, serta pemasaran digital. Evaluasi akhir menunjukkan kapasitas produksi meningkat 30%, efisiensi produksi naik 35%, pemasaran digital meningkat dari 10% menjadi 40%, dan 75% anggota mitra mulai menerapkan pencatatan keuangan sederhana. Selain itu, level keberdayaan mitra pada aspek produksi serta manajemen-pemasaran meningkat dari skor 1 menjadi 3 berdasarkan hasil observasi dan evaluasi pendampingan. Kebaruan program terletak pada pengembangan model inovasi rumput laut berbasis komunitas pesisir yang mengintegrasikan teknologi tepat guna, penguatan kompetensi kewirausahaan, dan kesiapan kelembagaan usaha kolektif melalui rintisan Kelompok Usaha Bersama. Temuan ini menunjukkan bahwa inovasi produk berbasis potensi lokal dapat memperkuat daya saing UMKM pesisir dan menjadi dasar replikasi program pemberdayaan serupa pada komunitas pesisir lainnya.